Предмет: Математика,
автор: margarita05072008
3) (x+3)2 + (x – 4)2 = 2 (4 – x)(x + 3).
!!!!!!!
Ответы
Автор ответа:
0
(х+3)²+(х-4)²=2(4-х)(х+3)
х²+6х+9+х²-8х+16=2(4х+12-х²-3х)
2х²-2х+25‐2(х+12-х²)=0
2х²-2х+25-2х-24+2х²=0
4х²-4х+1=0
(2x-1)²=0
2x-1=0; 2x=1; x=1/2.
Автор ответа:
0
Ответ:
Смотри решение на фото
Приложения:
Похожие вопросы
Предмет: Физика,
автор: сдохнивмуках
Предмет: Математика,
автор: golubeva8917
Предмет: История,
автор: wepaSka
Предмет: Русский язык,
автор: СуперОФИ1234567890
Предмет: Математика,
автор: Amirr1